Characterization of Burkholderia cepacia Complex Core Genome and the Underlying Recombination and Positive Selection - Zhou, Jianglin; Ren, Hongguang; Hu, Mingda; Zhou, Jing; Li, Beiping; Kong, Na; Zhang, Qi; Jin, Yuan; Liang, Long; Yue, Junjie (Frontiers in Genetics, 2020)
Recombination and positive selection are two key factors that play a vital role in pathogenic microorganisms’ population adaptation and diversification. The Burkholderia cepacia complex (Bcc) represents bacterial species with high similarity, which can cause severe infections among cases suffering from the chronic granulomatous disorder and cystic fibrosis (CF). At present, no genome-wide study has been carried out focusing on investigating the core genome of Bcc associated with the two evolutionary forces. The general characteristics of the core genome of Bcc species remain scarce as well. In this study, we explored the core orthologous genes of 116 Bcc strains using comparative genomic analysis and studied the two adaptive evolutionary forces: recombination and positive selection. We estimated 1005 orthogroups consisting entirely of single copy genes. These single copy orthologous genes in some Cluster of Orthologous Groups (COG) categories showed significant differences in the comparison of several evolutionary properties, and the encoding proteins were relatively simple and compact. Our findings showed that 5.8% of the core orthologous genes strongly supported recombination; in the meantime, 1.1% supported positive selection. We found that genes involved in protein synthesis as well as material transport and metabolism are favored by selection pressure. More importantly, homologous recombination contributed more genetic variation to a large number of genes and largely maintained the genetic cohesion in Bcc. This high level of recombination between Bcc species blurs their taxonomic boundaries, which leads Bcc species to be difficult or impossible to distinguish phenotypically and genotypically.